Epilepsy: Cognitive Function Impacts and Neuropsychological Approaches in Intervention - A Narrative Review - Apriasari, Hastinia; Arrisha, Mutia; Raharja, Belladina Nadyarinda; Mubarok, Muhammad Abdullah; Sulastri, Augustina; Kusrohmaniah, Sri (PROMOTOR, 2025)
Epilepsy is a chronic neurological disorder that affects cognitive function, emotions, and behavior. Limitations in cognitive function in people with epilepsy have a significant impact on the patient's quality of life. The neuropsychological approach plays an important role in the diagnosis of epilepsy, especially in identifying cognitive and emotional disorders that often accompany epilepsy. This study aims to describe the impact of epilepsy on cognitive function and evaluate the effectiveness of various neuropsychological interventions. The narrative review method was used in this literature review, by reviewing seven literatures obtained from two primary databases, namely PubMed and Proquest. The results showed that significantly impacted cognitive function by epilepsy including general intelligence, executive function, memory, and attention. Several interventions for epilepsy have shown the effectiveness of drug therapy such as corticosteroids and anakinra, non-invasive interventions such as external trigeminal nerve stimulation (ETNS), and innovative therapy using LEGO® in reducing seizure frequency and improving cognitive function.